2003
DOI: 10.1083/jcb.200211002
|View full text |Cite
|
Sign up to set email alerts
|

Synapse formation is regulated by the signaling adaptor GIT1

Abstract: Dendritic spines in the central nervous system undergo rapid actin-based shape changes, making actin regulators potential modulators of spine morphology and synapse formation. Although several potential regulators and effectors for actin organization have been identified, the mechanisms by which these molecules assemble and localize are not understood. Here we show that the G protein–coupled receptor kinase–interacting protein (GIT)1 serves such a function by targeting actin regulators and locally modulating R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
234
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(266 citation statements)
references
References 38 publications
30
234
0
1
Order By: Relevance
“…upon ephrinA1-Fc stimulation and colocalizes well with EphA2 ( Figure 7B). The synaptic localizing domain of Git1 was previously identified as being responsible for its localization to neuronal synapses (Zhang et al, 2003). In MDCK cells, however, we found that Git1⌬SLD-FLAG, which lacks the synaptic localizing domain, is still able to localize to cell-cell contacts, although with a lower efficiency than that of intact Git1-FLAG (Figure 7, B and C).…”
Section: Subcellular Distribution Of Git1 and Epha2 In Mdck Cellsmentioning
confidence: 70%
See 1 more Smart Citation
“…upon ephrinA1-Fc stimulation and colocalizes well with EphA2 ( Figure 7B). The synaptic localizing domain of Git1 was previously identified as being responsible for its localization to neuronal synapses (Zhang et al, 2003). In MDCK cells, however, we found that Git1⌬SLD-FLAG, which lacks the synaptic localizing domain, is still able to localize to cell-cell contacts, although with a lower efficiency than that of intact Git1-FLAG (Figure 7, B and C).…”
Section: Subcellular Distribution Of Git1 and Epha2 In Mdck Cellsmentioning
confidence: 70%
“…Git1 has been shown to localize and function at cell-cell junctions formed in neuronal synapses (Zhang et al, 2003) and immune synapses (Phee et al, 2005). However, these studies have mostly dealt with Git1 as a scaffold protein, which links cell surface receptors to the Pix-Pak pathway to remodel actin cytoskeletal architecture and stabilize these cell-cell junctions.…”
Section: Discussionmentioning
confidence: 99%
“…bPIX regulates formation of protrusions (14,(37)(38)(39), and overexpression of bPIX in fibroblasts and neurons alters the localization of bPIX itself, GIT1, Rac activity, and protrusions from a single leading edge to all around the cell periphery (37,39). Moreover, increased Rac activity in fibroblasts and epithelial cells correlates with multiple peripheral lamellae, or protrusions, and increased random motility (40).…”
Section: Discussionmentioning
confidence: 99%
“…Par ailleurs, les protéines GIT1 semblent impliquées avec Rac et PAK dans la formation des protrusions [20]. L'implication de GIT dans la formation des synapses et la morphologie des dendrites a également été suggérée [21]. Sur le plan physiopathologique, une étude récente vient de mettre en évidence une interaction entre GIT1 et la protéine hungtingtine et a démontré la dégradation spécifique de GIT1 au cours du développement de la maladie de Huntington [22].…”
Section: Git : Une Famille De Protéines Gap Pour Les Gtpases Arfunclassified